Routes of Human Rabies Infection and Prophylaxis as Methods of Prevention - Dąbrowski, Kacper; Leśniewska, Natalia; Szymulewicz , Bartłomiej; Łukaszewicz , Jakub; Niewęgłowska , Małgorzata; Walczak , Paulina; Bender , Aleksandra; Widomska , Katarzyna; Bernad , Mateusz; Krazińska , Oliwia; et al. (Quality in Sport, 2026)
The rabies virus is responsible for one of the most severe diseases transmitted from animals to humans. Rabies is associated with an almost 100% case-fatality rate once clinical symptoms develop. The aim of this study is to present the principal routes of rabies virus transmission to humans and to discuss strategies for limiting viral spread through preventive measures, based on the available literature concerning the pathogenesis, epidemiology, and prophylactic methods applied in both animals and humans. The primary route of transmission to humans is a bite from an infected animal. However, other, less common routes of infection are also possible, including contact of secretions from an infected animal with mucous membranes or damaged skin. Extremely rare cases of transmission have also been reported through aerosol exposure or through organ transplantation from an infected donor. In Europe, wild animals constitute the main reservoir of the rabies virus, with particular emphasis on foxes, highlighting the critical role of oral vaccination programs targeting these species. Vaccination of domestic animals, as well as pre-exposure and post-exposure prophylaxis in humans, also remain essential components of rabies prevention. A multidisciplinary approach to rabies control, integrating the efforts of veterinary and medical services through infection control in animal populations, improved access to vaccines and rabies immunoglobulin, and increased public awareness regarding the disease, its transmission routes, and preventive measures, may ultimately contribute to the complete elimination of human rabies in the future.